Technology and Culture: Ruminations on Marshall Mc Luhan’s ‘The Mechanical Bride’ - Singh , Ravindra Pratap (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
In his observation of North American culture industry Marshal Mc Luhan finds that how the trained human minds affect the collective public minds and influence them in their own way . The controlled popular culture offers various meanings to different stakeholders . Marshal Mc Luhan’s ‘The Mechanical Bride’ appears as a chapter in the his book The Mechanical Bride: Folklore of Industrial Man , and offers significant inferences on the influence of technology in the life of common individual , and subsequently makes the indicators of the popular culture. The present papers offers the key indicators and findings in Marshal Mc Luhan’s ‘The Mechanical Bride’.